Should potential for climate change refugia be mainstreamed into the criteria for describing EBSAs? - David Edward Johnson; Ellen Lorraine Kenchington (Conservation Letters, 2019)
Abstract The world's oceans are subject to the influence of climate change at all latitudes and depths. There is a growing body of literature on the responses of species to climate change, which has a strong deterministic component indicating that responses can be predicted. At the same time, advances in oceanographic data acquisition and modeling have facilitated the identification of potential climate change refugia. The Convention on Biological Diversity's “Voluntary Specific Workplan on Biodiversity in Cold‐Water Areas within the Jurisdictional Scope of the Convention” explicitly calls for the identification and protection of refugia in cold‐water areas. We propose adding “Climate Change Refugium” as an integral consideration for identification of Ecologically or Biologically Significant Marine Areas (EBSAs). We provide a description of this as a potential eighth criterion. We then briefly discuss the pros and cons of introducing this eighth criterion, or an alternative strategy to develop guidelines that explicitly link refugia to the rationale of existing EBSA criteria, in the hope that this opinion piece will launch further discussion on this notion.